Expand the class and transform the agentic engagement of future trainers - Rigo, Daiana Y. (2022)
The study presented aims to promote and understand the agent commitment of students, future educators, in initial education through an expanded educational experience in order to proactively rethink their professional role. Participated 41 students from the Faculty and the Bachelor of Initial Education, who were studying the third year of the career at the National University of Río Cuarto, Argentina. Under an interpretive qualitative design, an expansive educational experience was designed so that students could proactively rethink their professional role from their agencies, based on an activity that proposed going to the territory, specifically, walking the city, in search of art to teach. Data were collected in three moments, during the investigation almost finished and already concluded. The results show that students develop proactive actions and emotions that motivate rethinking the teaching role, as well as new teaching perspectives in transformation from the recognition and educational construction of new territories and perspectives of being a teacher. What was found shows the importance of rethinking initial teacher training in order to promote training instances aimed at fostering agent commitment, active participation and the initiative to innovate professional practice.